Tindak Tutur Ilokusi dalam Cerpen Karma Tanah Karya Ketut Syahruwardi Abbas - Moh. Adek Agustian S.; Subaidi Subaidi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines illocutionary speech acts according to Austin's theory in the short story Karma Tanah by Ketut Syahruwardi Abbas. This study aims to describe the form of illocutionary speech acts in the short story Karma Tanah by Ketut Syahruwardi Abbas, to describe the contextual meaning in the short story Karma Tanah by Ketut Syahruwardi Abbas. This study uses a qualitative research type with a descriptive method. The research data used are dialogues in the form of words, phrases, clauses, and sentences that indicate illocutionary speech acts. The source of research data is the short story Karma Tanah by Ketut Syahruwardi Abbas. Data was obtained using the first technique, the researcher classified the data obtained during the reading stage, then grouped based on the form and meaning of the illocutionary speech found in the short story Karma Tanah by Ketut Syahruwardi Abbas. Furthermore, the researcher analyzed all groups of data based on the form and meaning of the illocutionary speech and finally the researcher made conclusions or described the data based on the results of the analysis. The results of this study were obtained with 17 speech data found divided into five types of illocutionary speech acts, namely assertive speech acts as many as 4 utterances, directive speech acts as many as 5 utterances, expressive speech acts as many as 3 utterances, commissive speech acts as many as 3 utterances, and declarative speech acts as many as 2 utterances. The meaning of the utterance is adjusted to the context of the utterance. From these results, the form of assertive and directive speech acts states that the most are found in the short story Karma Tanah.